Within- and between-session reliability of secondary hyperalgesia induced by electrical high-frequency stimulation - Cayrol, Timothée; Lebleu, Julien; Mouraux, André; Roussel, Nathalie; Pitance, Laurent; van den Broeke, Emanuel N (European journal of pain, 2020)
An increasing number of studies are focusing on secondary hyperalgesia to better understand central sensitization, as this phenomenon may play an important role in persistent pain. Recent studies have shown that, compared to the classical high-frequency stimulation protocol (HFS) at 100 Hz, a protocol using 42 Hz stimulation induces a more intense and a larger area of secondary hyperalgesia (SH). The aim of this study was to investigate the within- and between-session reliability of SH induced by this optimized HFS protocol. Thirty-two healthy subjects received HFS to their volar forearm in two sessions, separated by at least 2 weeks. SH was assessed by measuring the area size of increased sensitivity to pinprick stimuli after applying HFS, the sensitivity to pinprick stimuli after applying HFS and the change in pinprick sensitivity after versus before HFS. Assessments were made before HFS, and 30, 35 and 40 min after HFS. Relative and absolute reliability were analysed using intraclass correlation coefficients (ICCs), coefficients of variation (CVs), standard error of means (SEMs) and the minimum detectable changes (MDCs). The area of SH showed good to excellent within-session and between-session relative reliability (ICCs > 0.80), except for the change in pinprick sensitivity, which showed close to poor between-session relative reliability (ICC = 0.53). Furthermore, measures of absolute reliability generally demonstrated large between-subject variability and significant fluctuations across repeated measurements. HFS-induced hyperalgesia is suitable to discriminate or compare individuals but it may not be sensitive to changes due to an intervention. It is crucial to evaluate central sensitization adequately in humans. This study formally establishes the reliability of secondary hyperalgesia induced by electrical high-frequency stimulation. The results of this study will improve future studies investigating secondary hyperalgesia in humans.